2019
DOI: 10.1136/gutjnl-2018-317872
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor (GDNF) mediates hepatic stellate cell activation via ALK5/Smad signalling

Abstract: ObjectiveAlthough glial cell line-derived neurotrophic factor (GDNF) is a member of the transforming growth factor-β superfamily, its function in liver fibrosis has rarely been studied. Here, we investigated the role of GDNF in hepatic stellate cell (HSC) activation and liver fibrosis in humans and mice.DesignGDNF expression was examined in liver biopsies and sera from patients with liver fibrosis. The functional role of GDNF in liver fibrosis was examined in mice with adenoviral delivery of the GDNF gene, GDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…These findings indicate that the SMAD3-SMAD4 signaling pathway is the downstream effector that mediates the increased expression of GDNF and furin by TGF-β1 in hGL cells. In human hepatic stellate cells, knockdown of SMAD2/3 abolishes the TGF-β-induced increase in GDNF [57]. In human liver cells (HepG2 cells), the expression of furin is induced and regulated by TGF-β1 via the MEK/p42/p44 MAPK and SMAD2-SMAD4 signaling pathways [38].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the SMAD3-SMAD4 signaling pathway is the downstream effector that mediates the increased expression of GDNF and furin by TGF-β1 in hGL cells. In human hepatic stellate cells, knockdown of SMAD2/3 abolishes the TGF-β-induced increase in GDNF [57]. In human liver cells (HepG2 cells), the expression of furin is induced and regulated by TGF-β1 via the MEK/p42/p44 MAPK and SMAD2-SMAD4 signaling pathways [38].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, it is possible that GDNF functions as a trophic factor for hepatic neurons as well as executing direct effects on hepatic parenchymal and possibly non-parenchymal cells. Tao et al analyzed human liver tissue specimens and primary cell lines from human livers, and showed that GDNF is likely present in human HSCs as it is colocalized with α-smooth muscle actin positive cells (21).…”
Section: Glial Cell-line Derived Neurotrophic Factor and Non-alcoholimentioning
confidence: 99%
“…Similar results were seen in mouse fibrosis models. GDNF expression in the liver was increased by 2-4-folds in mice which received bile duct ligation or were fed with methionine-choline deficient diet, and by almost 13-fold in mice treated with CCl 4 (21). Whether the increase in GDNF plays a protective or exacerbating role in the pathogenesis of hepatic fibrosis remains elusive, and results are conflicting.…”
Section: Glial Cell-line Derived Neurotrophic Factor and Hepatic Fibrmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the use of the CRISPR/Cas9 site-specific nuclease system has revolutionized the therapeutic options for several diseases, and may also provide new opportunities for the treatment of liver fibrosis. A recent study showing the antifibrotic effects of the knock down of the glial cell line-derived neurotrophic factor (GDNF) using the CRISPR/CAs9 in an adeno-viral delivery system [85] illustrates an exciting development.…”
Section: Drugs To Be Targetedmentioning
confidence: 99%